IMPACT OF SPIRITUAL INTELLIGENCE ON ORGANIZATIONAL COMMITMENT AND WELL-BEING OF EMPLOYEES - Sania Shakeel; Anjum Afshan; Amina Sattar (Policy Research Journal, 2025)
The current study was held to investigate the impact of spiritual intelligence on organizational commitment and well-being of employees. It will provide an insight into the importance of spiritual intelligence in developing productive work environment and in enhancement of organizational commitment as well as well-being. Using the quantitative method of research, the researchers utilized Scale for Spiritual Intelligence (SSI) to measure spiritual intelligence, Organizational Commitment Questionnaire (OCQ) for organizational commitment and Warwick and Edinburgh Mental Well-being scale (WEMWBS) for evaluating well-being. The pilot study stated that the Cronbach‟s alpha of the Scale for Spiritual Intelligence (SSI) was 0.6, for the Organizational Commitment Questionnaire (OCQ) was 0.8 and for the Warwick and Edinburgh Mental Well-being scale (WEMWBS) the Cronbach‟s alpha reliability was 0.8. The results demonstrated a significant impact of spiritual intelligence on organizational commitment and well-being and significant gender differences was observed on organizational commitment and well-being in the sample. Interventions and therapies are utilized to enhance spiritual intelligence.